Human and Animal Pentastomiasis in Malaysia : Review - Bahaa Mohamed Abdul Latif; Azdayanti Muslim; Heo Chong Chin (Journal of Tropical Life Science, 2016)
Pentastomiasis is a zoonotic parasitic disease induced by the larval stages of pentasomes. The disease has been reported in Africa, the Middle East and Southeast Asia and caused by the nymphs of the two genera: Linguatula and Armillifer and the two species L. serrata and A. armillatus regard for more than 90% of human cases. The definitive hosts of Armillifer spp. are snakes, lizards and other reptiles. The parasites live in the upper respiratory tracts and lay eggs that are passed out through respiratory secretions, saliva or faeces. Intermediate hosts are humans, rodents and other mammals. Humans incidentally acquire the infestation by the consumption of uncooked infested snake meat or by drinking water contaminated with ova of the pentastomes. In the intestinal tract, the larvae hatch from the ova, penetrate the intestinal wall and migrate to organs in which the liver is the most common site. Human pentastomiasis was reported among aborigines in West and East Malaysia. Armillifer moniliformis was identified in wild animals and carnivores with infection rate 1.8% and 20.7% respectively. The adults of pentostomes (A. moniliformis) were recovered from two out of six snakes Python reticulates. Recently a case of human pentastomiasis was reported in Sabah, East Malaysia, caused by nymph of Armillifer moniliformis.